Mass Gathering Medicine New discipline to Deal with Epidemic and Infectious Diseases in the Hajj Among Muslim Pilgrimage A Mini Review Article - Turki, Yousef Abdullah Al (2016)
Mass Gathering Medicine is one of the new disciplines in Medicine which deal with all health aspects in overcrowded areas. Mass Gathering Medicine is an important new challenging discipline which needs to be supported by all concern experts such as the World Health Organization, Centers for Disease Control and Prevention, ministries of health from all countries, universities, research centers, and all other experts in this field. Scientist and academic staffs from all countries should be encouraged to participate in narrowing the gap of knowledge for Mass Gathering Medicine. Postgraduate board or fellowship certificate should be encouraged internationally.
Keywords: Discipline; Hajj; Mass Gathering Medicine; Prevention